Implementation of Islamic Religious Education Teacher Performance Monitoring at Junior High School - Yudi Nur Supriadi; Irpan Irpan; Maria Assumpta Wikantari; Apit Fathurohman; Asep Sugara (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article examines the effect of implementing Islamic Religious Education (PAI) academic supervision on the performance of PAI teachers in junior high schools (SMP). This research uses a qualitative approach with a case study method in two junior high schools in Barito Kuala Regency, South Kalimantan Province. The research data were collected through observation, interviews, and documentation and analyzed using the Kirkpatrick evaluation model. The results showed that PAI academic supervision in junior high schools is still not optimal because various factors, such as competence, motivation, work environment, and facilities, influence it. However, PAI academic supervision also positively impacts the performance of PAI teachers in junior high schools, such as improving the quality of learning, developing student potential, and job satisfaction. This article provides recommendations for PAI supervisors, principals, PAI teachers, and other relevant parties in improving PAI academic supervision in junior high schools, as well as a reference for future research related to the same or similar topics.